Bulan Sabit di Negeri Komunis Tirai Bambu: Sebuah Perjuangan Identitas Umat Minoritas - Mashar, Aly (SHAHIH: Journal of Islamicate Multidisciplinary, 2018)
Chinese Moslems are mostly ethnic Hui and Uyghur. Ethnic Hui Moslems live in cities in China such as Beijing, Xi'an, Guangzhou, Tianjin and Shanghai, while ethnic Uyghurs tend to stay concentrated in an area, especially in Xinjiang. The sect which is followed by Chinese Moslems are Sunny and Syiah Imamiyah, based on Hanafiyah and Syafi'ah jurisprudence, and following a number of tarekat, such as Qadiriyyah, Kubrawiyyah, Jahriyyah, and Khuffiyyah. Muslims tend to be more peaceful than ethnic Uyghurs, not even to the point of causing war. Even so, there are often feuds with Han ethnicity, Chinese Muslim civilization can be said to be quite advanced, especially related to education, transliteration and translation of the Qur'an into Chinese, calligraphy art; architecture, ornamentation, mosque construction; economy and commerce; and several scientific branches.